Vasoconstrictive effect of arachidonic acid on aortic ring of rabbit - Wang Shi-Jiu; Sevy Roger; Salganicoff Lion (Acta Pharmacologica Sinica, 2016)
It has been demonstrated that rings of rabbit thoracic aorta with intact endothelium contracted in response to arachidonic acid (AA) in a dose-effect dependent manner (ED=12μmol/L). The contractile response by AA was inhibited by cycloxygenase inhibitor, indomethacin 10μmol/L. Rings of rabbit aorta in precontracted state affected by phenylephrine showed an additional contraction in response to AA. Rabbit aorta without endothelium did not show any response to AA (l μmol/L). Aorta with or without endothelium contracted to the same extent in response to thromboxane A receptor agonist, SQ 26655 (0.1 μmol/L). The contraction caused by AA 10 μpmol/L was not completely inhibited by indomethacin or aspirin, but was inhibited by a lipoxygenase inhibitor, BW 755 c 30 μmol/L. We conclude that the intact endothelium of aorta is greatly responsible for the contraction of smooth muscle of rabbit aorta by AA, and the contraction of aorta by AA is mediated by cycloxygenase and lipoxygenase metabolites.